2014
DOI: 10.1007/s12170-014-0407-4
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Blood Levels Clinical Significance Update

Abstract: The potential benefit of fish oil (omega-3 fatty acids) consumption to reduce cardiovascular disease (CVD) risk remains controversial. Some investigations report reduced CVD risk associated with fish or fish oil consumption while others report no benefit. This controversy is in part resolved when consideration is given to omega-3 blood levels in relation to CVD risk as well as blood levels achieved in clinical trials of omega-3 supplementation and CVD benefit. There is a wide variation in omega-3 blood levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 44 publications
0
49
0
1
Order By: Relevance
“…In the Japan EPA lipid intervention study, 13) the use of EPA-E increased the EPA/AA ratio from 0.6 to 1.3, and significantly reduced the recurrence of cardiovascular events. As for the appropriate value of the ontreatment EPA/AA ratio, Superko, et al suggested a value of > 0.75 in their review; 14) however, there was a large difference between the results from studies in other western countries and Japan. The on-treatment EPA/AA ratio of Japanese studies The on-treatment EPA/AA ratio reached the target value of 0.92 in all but one patient.…”
Section: Discussionmentioning
confidence: 99%
“…In the Japan EPA lipid intervention study, 13) the use of EPA-E increased the EPA/AA ratio from 0.6 to 1.3, and significantly reduced the recurrence of cardiovascular events. As for the appropriate value of the ontreatment EPA/AA ratio, Superko, et al suggested a value of > 0.75 in their review; 14) however, there was a large difference between the results from studies in other western countries and Japan. The on-treatment EPA/AA ratio of Japanese studies The on-treatment EPA/AA ratio reached the target value of 0.92 in all but one patient.…”
Section: Discussionmentioning
confidence: 99%
“…The health benefits of n-3 polyunsaturated fatty acids (n-3 PUFAs) on cardiovascular diseases have been reported by numerous studies (see reviews [77,78]), even if results still remain controversial [77]. n-3 PUFAs are a family of biologically active fatty acids.…”
Section: Nutritional Approachmentioning
confidence: 99%
“…Following this line of thought and given traditional treatment methods, an important issue which may be incorporated into the difficult task of preventing cardiovascular abnormalities that may culminate in sudden cardiac death in OSA individuals with epilepsy, is the use of omega-3 fatty acid (omega-3 FA) supplementation or regular fish consumption [28,29]. It is quite likely that one of the early reports of fish consumption as a medical therapy was described in the Old Testament book of Tobias, "Then the angel said to him: Take out the entrails of the fish, and lay up his heart, and his gall, and his liver for thee; for these are necessary for useful medicines" [30,31]. Nowadays it is well established that the human body is not able to synthesize omega-3 FAs; therefore, people should get it from a diet rich in specific types of fish to provide positive impact on the health system [32][33][34][35].…”
Section: To the Editormentioning
confidence: 99%